A galactic Easter! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack., 2014)
Zack and Drake venture to Gluco, the candy planet, for some Easter fun but while competing in such activities as an egg toss and a three-legged race, Zack is so determined to come in first that he considers cheating to win.